Impaired T-Cell Function in B-Cell Lymphoma: A Direct Consequence of Events at the Immunological Synapse? - Nassef Kadry Naguib Roufaiel, Marian; Wells, James W.; Steptoe, Raymond J. (Frontiers in Immunology, 2015)
Tumours can escape immune destruction through the development of antigen loss variants and loss of antigen processing/presentation pathways thereby rendering them invisible to T cells. Alternatively, mechanisms of peripheral T-cell tolerance that would normally be important for protection from the development of autoimmunity may also be co-opted to i) generate an immuno-inhibitory tumour environment, ii) promote development of regulatory cell populations or iii) cell-intrinsically inactivate tumour-specific T cells. Emerging evidence suggests that T-cell function is impaired in haematological malignancies which may manifest from cognate interactions between T cells and the tumour. The immunological synapse forms the cognate T-cell and antigen-presenting cell interaction and is the site where key signalling events, including those delivered by co-inhibitory receptors, that determine the fate of T cells occur. Here we review evidence that events at the immune synapse between T cells and malignant B cells and alterations in immune synapse function may contribute to loss of T-cell function in B-cell malignancies.